Penerapan Teknik Relaksasi Nafas Dalam terhadap Intensitas Nyeri dengan Asuhan Keperawatan Post Op Apendiktomi di Ruangan Bedah Rumah Sakit Umum Daerah Palembang Bari - Tuty Elyta; Miming Oxyandi; Agustin Mardalena (Pusat Riset dan Inovasi Nasional, 2025)
Background : Appendectomy is a surgical procedure to remove the appendix which is done as soon as possible to reduce the risk of perforation. Nursing problems that arise after appendectomy is acute pain. Objectives: Gaining real experience and knowledge and being able to document the application of deep breathing relaxation techniques is an appropriate non-pharmacological action in reducing pain scale. Method: this type of scientific paper uses a descriptive method with a descriptive case study approach with a case study approach to explore the problem of nursing care carried out on two patients carried out on June 15 - 20 2021. Results: from the results of nursing care to Mrs